Antifungal Activity of Endemic Satureja icarica - Dulger, Basaran; Hacioglu, Nurcihan (Asian Journal of Chemistry, 2010)
The methanol extract obtained from Satureja icarica P.H. Davis (Lamiaceae) have been investigated for their antifungal activity. Antifungal activity was determined with Candia albicans, Candida tropicalis, Candida guilliermondii, Cryptococcus neoformans, Cryptococcus laurentii, Aspergillus flavus, Aspergillus niger, Alternaria alternate, Geotrichum candidum, Fusarium oxysporum, Penicillium frequentans, Penicillium canescens and Botrytis cineriae by the well-in-agar method and the visual broth macrodilution method. The diameter of inhibition zones varied from 11.6 to 18.8 mm. The MIC values ranged from 6.25 to 25 μg/mL. The extracts exhibited a strong antifungal effect against the tested fungi. Candida albicans is more susceptible to the extract. The present findings provide a support to the use of this plant in traditional medicine for fungal infections especially against candidiasis.